Evaluating the impact of employment protection on firm-provided training in an RDD framework - Thomas Bolli; Johanna Kemper (ETH Zurich, KOF Swiss Economic Institute, 2017)
This paper tests the hypothesis that employment protection legislation (EPL) increases the incentives of firms to train their employees. The identification strategy uses a regression discontinuity design (RDD) that exploits exemptions of small firms from EPL. Using firm-level data from Finland and Italy in 2005 and 2010, we do not find empirical evidence that EPL increases the propensity to train or the intensity of firm-provided training. The estimates remain insignificant throughout and mostly have a negative sign. This result is supported in a heterogeneous treatment setting that exploits variation in sector-specific employment volatility. Hence, though the upper bounds of the estimates include economically significant effects, we conclude that EPL has no effect on training of small firms in Finland and Italy.
Keywords: J24; K31; 330; Employment Protection; Training; Regression Discontinuity; Difference-in-Discontinuity